KREATIVITAS KONSELOR DALAM PENGEMBANGAN MEDIA BIMBINGAN DAN KONSELING IMPACT - ismail taufik (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
Impact counseling is a new approach in the counseling field. Imapct counsling emphazies a multi sensory approach that involves verbal, visual, and kinesthetic dimensions in the counseling process. This research aims to discribe various unique approaches to counseling that seek to integrate various concepts ina rational emotive behavior therapy (REBT), transactional analysis (TA), gestalt,and reality therapy by using various properties, images, and motions in the counseling process. So that impact counseling demands the creativity of counselors in the developing guidance and counseling media using avariety of simple media. This study uses a type of qualitative research with instrumental case study using visual aids. Data collection techniques in this study include documentation, observation, and interviews. The results of this study indicate that the therapeutic process in impact counseling seeks to make counseling sessions more effective, active, and short. Guidance and counseling media development can use simple media such as “bucket vessel”. That are four stages that need to be passed in the impact counseling process by using the bucket vessel media, namely : (1) Rapport, which shows the phase of building a genuine and trusting relationship between the counselor and the counselee, (2) Contract, refers to an agreement either implicity or explicity between the counselor and counselee in the setting the goals of entire counsling session or part of counseling session. (3 Focus, the focus phase resfers to the stage that focuses an a particular topic or issue within a certain period of time, (4) Funnel , the funnel phase refers to stage of discusing an issue ina certainway until a new deeper level of understanding (insight) is achived. The phases and stages of impact counseling process as above are usually abbreviated as RCFF. Trough the development of media in the impact counseling process counselor can help counselee formulate and set priorities, both short term,medium term, or long term in a more enjoyable and meaningful way. Then the counselee can determine what actions must be taken to achive the goals to be achieved in his life.